2005
DOI: 10.1515/hf.2005.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pinus taeda L. wood property calibrations based on NIR spectra from the radial-longitudinal and radial-transverse faces of wooden strips

Abstract: When a radial strip is cut from an increment core it can potentially be cut with two orientations: parallel to longitudinal tracheids, i.e., a radial-longitudinal (RL) strip (the orientation of SilviScan samples), or at an orientation of 908 to the tracheids, i.e., a radial-transverse (RT) strip. Both strips could be used for near-infrared (NIR) analysis, but it is unknown how calibrations based on RT-face NIR spectra compare with those based on RL-face NIR spectra. A total of 20 Pinus taeda L. (loblolly pine)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 14 publications
0
21
3
Order By: Relevance
“…lumber from spectra collected on transversal sections were better than models based on spectra acquired over tangential or radial sections. The difference between transversal and radial measurements was lower in the case of density estimation (Schimleck et al 2005, Defo et al 2007, Fujimoto et al 2008. Tsuchikawa et al (1996a) explained the difference between tangential and transversal measurements by the fact that when scanning the transversal section, the incident radiation directly interferes with the free water present in the lumen of the cell, while it is not the case when scanning the tangential or the radial section since the radiation will first encounter the cell wall.…”
Section: Principles Of Nir Spectroscopymentioning
confidence: 99%
“…lumber from spectra collected on transversal sections were better than models based on spectra acquired over tangential or radial sections. The difference between transversal and radial measurements was lower in the case of density estimation (Schimleck et al 2005, Defo et al 2007, Fujimoto et al 2008. Tsuchikawa et al (1996a) explained the difference between tangential and transversal measurements by the fact that when scanning the transversal section, the incident radiation directly interferes with the free water present in the lumen of the cell, while it is not the case when scanning the tangential or the radial section since the radiation will first encounter the cell wall.…”
Section: Principles Of Nir Spectroscopymentioning
confidence: 99%
“…The aim of this treatment was also to conserve the wood prior to NIR measurement and future nondestructive analyses. Schimleck et al (2003) removed extractives in wood samples by extracting them during 18 h with warm acetone (C 3 H 6 O) containing C=O double bonds and C-H bonds.…”
Section: Wood Samples and Determination Of Wood Propertiesmentioning
confidence: 99%
“…The Q 2 gives the amount of explained variation and is dimensionless as is the ratio of performance to deviation (RPD), which reflects the predicative ability of the calibration. RPD values based on independent test sets and in the range of 1.5-2.5 indicate that calibrations can be used for coarse screening purposes (Schimleck et al 2003). Values >2.5 are satisfactory for screening, whereas models with RPD values >10 have excellent performance (Williams and Sobering 1993).…”
Section: Model Diagnostics and Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationship between the NIR spectra and the surface roughness has been studied for Pinus taeda (Schimleck et al 2005). The cited study reported that surface roughness contributed to weaker statistics and that the surface roughness of Pinus taeda has a weak influence on the effect of models built by the NIR data.…”
Section: Introductionmentioning
confidence: 99%